2017
DOI: 10.1038/s41467-017-00933-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation in a range of mTOR-related genes associates with intracranial volume and intellectual disability

Abstract: De novo mutations in specific mTOR pathway genes cause brain overgrowth in the context of intellectual disability (ID). By analyzing 101 mMTOR-related genes in a large ID patient cohort and two independent population cohorts, we show that these genes modulate brain growth in health and disease. We report the mTOR activator gene RHEB as an ID gene that is associated with megalencephaly when mutated. Functional testing of mutant RHEB in vertebrate animal models indicates pathway hyperactivation with a concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 69 publications
(79 reference statements)
13
79
0
Order By: Relevance
“…Accordingly, many ASD genes are synaptic proteins, chromatin remodelers, or FMRP targets, that is genes encoding transcripts that bind to FMRP (Iossifov et al, ). Alterations of the same classes of protein functions and biological processes involved in neuronal development, such as the mammalian target of rapamycin (mTOR) pathways, GABA receptor function or glutamate NMDA receptor function, have been also found implicated in ID, epilepsy, and schizophrenia (Cristino et al, ; Endele et al, ; Gilman et al, ; Krumm et al, ; Paoletti, Bellone, & Zhou, ; Reijnders et al, ). The multiple genes and molecular pathways shared by ID, ASD, and other developmental or psychiatric disorders indicate a common origin that explains the co‐occurrence of these conditions (Barabási, Gulbahce, & Loscalzo, ; Cukier et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many ASD genes are synaptic proteins, chromatin remodelers, or FMRP targets, that is genes encoding transcripts that bind to FMRP (Iossifov et al, ). Alterations of the same classes of protein functions and biological processes involved in neuronal development, such as the mammalian target of rapamycin (mTOR) pathways, GABA receptor function or glutamate NMDA receptor function, have been also found implicated in ID, epilepsy, and schizophrenia (Cristino et al, ; Endele et al, ; Gilman et al, ; Krumm et al, ; Paoletti, Bellone, & Zhou, ; Reijnders et al, ). The multiple genes and molecular pathways shared by ID, ASD, and other developmental or psychiatric disorders indicate a common origin that explains the co‐occurrence of these conditions (Barabási, Gulbahce, & Loscalzo, ; Cukier et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To further study the mechanisms of epileptogenesis and hyperexcitability in mTORopathies vs GATORopathies, a plasmid encoding a constitutively active form of the mTOR activator Rheb (Rheb CA ,) was introduced to the fetal mouse brain by in utero electroporation. Rheb was selected for comparative genetic manipulation because two recent studies have reported gain‐of‐function mutations in RHEB leading to MCD associated with epilepsy and because Rheb integrates both the canonical growth factor signaling vector and the ATP‐AMP‐AMPK‐dependent vector, thus allowing comparison with the amino acid signaling arm of the mTOR pathway. In addition, from a methodologic perspective, Rheb CA expression rapidly (6‐8 hours) activates the mTOR pathway as compared to other experimental strategies such as conditional transgenic mice, small hairpin RNA (shRNA), or CRISPR/Cas9 vectors because the timing of mTORC1 activation depends on the half‐life of the KD/KO protein of interest.…”
Section: Epileptogenesis and Mtor‐gator Signalingmentioning
confidence: 99%
“…Specifically, we observed that these genomic regions are significantly enriched for an mTOR signaling gene set as well as for genes involved in cholesterol metabolism (see Figure 6a and Table S10). Regarding the mTOR gene set, the MTOR gene is itself an intellectual disability gene that has been intimately linked to brain development 84,85 . Regarding the cholesterol metabolism gene set, the brain contains approximately 25% of the body's cholesterol (mostly as a component of the myelin sheaths that surround axons) 86,87 with defects in brain cholesterol metabolism being linked to central nervous system disease 88,89 , and BCL11A has recently been shown to influence (and be influenced by) lipid levels [90][91][92] .…”
Section: Analysis Of 46 Diseases and Complex Traitsmentioning
confidence: 99%